OPTIMALISASI MANAJEMEN KEUANGAN DENGAN SISTEM PENERIMAAN KAS BERBASIS MICROSOFT ACCESS PADA KOS ANNISA: SEBUAH INOVASI UNTUK EFISIENSI BISNIS - Sanda Patrisia Komalasari; Nurul Ulfah Primadini; Wulandari Putri Shayen; Annisa Rana Tsabitah; Annisa Pratiwi; Saskia Fadhilla; Yola Yulianita (Jurnal Hilirisasi IPTEKS, 2024)
Computerized recording systems are much more efficient than manual recording systems. An automated recording system will be able to save paper and make it easier to search for the desired data. In the boarding house business, where many children rent rooms, the manual recording system often encounters difficulties determining when rent payments are due and tracing who still needs to pay the rent. This service activity aims to help solve these problems. This service aims to create a simple system related to the cash receipts of tenants who rent boarding houses. The cash receipt system design is created using Microsoft Access. The system is designed for use at the Annisa boarding house, an MSME located in the Jati area of Padang City. The service activity stages begin with analyzing user needs, then continue with system design, and end with introducing the system to users to apply in their business. This system is beneficial for boarding house businesses, especially Kos Annisa. This service activity is part of the project-based learning system in the System Design Analysis course in the Bachelor of Accounting Study Program at Andalas University. This system can be developed to be better and used by MSMEs operating in other boarding houses. Adding more comprehensive features related to recording related to the boarding house business and making it a web-based system is a development plan that can be carried out in the future.